(untitled) (African Journal of Biomedical Research, 2019)
Malaria is the most important parasitic disease of subtropical and tropical countries and its control remains serious challenge, especially through the development of parasite resistance to standard antimalarial drugs. Aqueous and methanol leaves extract of Glyphaea brevis were investigated for their activities against malaria infections using albino mice infected with Plasmodium berghei at dose levels of 100mg/kg, 200mg/kg and 300mg/kg per day. Artemisinin at 5mg/kg /day was used as standard control. Dose dependent chemo-suppression of the parasites was obtained at different dosages of the tested extract. The methanol extract was found to be more active in parasite inhibition growth than its aqueous counterpart. In the established infected control group, aqueous and methanol extracts both showed significant dose dependent (P< 0.05) inhibitory and suppressive activities on the extracts treated animals when compared with the infected (positive) control groups. The percentage suppression revealed that 400 mg/kg methanol extract treated group had the highest efficacy (81.89%) amongst the various dosages administered. There was reduction in PCV levels in all the Plasmodium berghei infected mice when compared to the normal control group. Also, there were significant (P< 0.05) increase in the serum concentration of alanine aminotransferase (80.75 ± 7.04) and aspartate aminotransferase (68.50 ± 4.66) of the infected control group compared to normal, standard and the extract treated groups. There was significant difference in the serum concentration of alkaline phosphatase in the positive control group and aqueous extract treated groups. Conclusively, aqueous and methanol leaves extracts of G. brevis possess antiplasmodial activity.